Perempuan Berhijab dalam Konten Hijab Profile di Portal Wolipop: Analisis Semiotika Roland Barthes - Umi Khoirum (Institut Agama Islam Negeri Bengkulu, 2020)
Hijab is currently interpreted as part of women's fashion, to complement thebeauty of clothes worn everyday. Many factors have caused a shift in themeaning of hijab for women. Some of the factors include trends. This study aimsto reveal the role of the media, especially in the Wolipop portal, as an onlinemedia that packages women's lives in various aspects including the hijab profilein building the trend of women's hijab. In an effort to reveal this shift, thewriter uses the theory of Roland Barthes as a knife to analyze the depiction ofhijab women. The data were collected using purposive sampling method ofarticles on the hijab profile content in Wolipop. Based on the research results, itis known that in its development, the media presents women who are able tomake the hijab not only a sign of Muslim women, but women who wear hijabhave been able to appear in the public with various achievements that have led tothe latest hijab fashion models. And online media consciously package howwomen are free to express themselves with their hijab according to theirprofession, age, interests and preferences.